Environmental Considerations in Dysphagia Care: Exploring the Relationship Between Dysphagia and Food Security. - Beltrán, Jessica; Shune, Samantha (Perspectives of the ASHA Special Interest Groups, 2025)
Purpose: Older adults are at high risk for malnourishment due to age-related changes in nutritional absorption, greater propensity for chronic illness, and higher rates of function-limiting disability. Dysphagia is also more frequent in older adults secondary to a variety of acquired health conditions. The cognitive and physical impairments that often co-occur with dysphagia pose an additional barrier to food procurement and preparation. These vulnerabilities put these individuals at greater risk of food insecurity, the term used to describe the uncertain access to adequate food and nutrition. Beyond factors related to health and bodily function that heighten risk of food insecurity, so do policy-mediated factors that create environmental, social, and financial barriers to secure access to food and nutrition. Despite this relationship between dysphagia and food security, very limited research has been conducted on the role of food security in dysphagia care. Method: This tutorial explores the multifactorial barriers to food access that older adults with disabilities face and the impact on health outcomes using the Ecological Paradigm of Functioning and Disability, a novel hybrid model that recognizes the complex sociocultural forces that impact functioning and disability in older adults. This model is utilized to discuss the implications on dysphagia treatment and validity considerations of using the Hunger Vital Sign with older adults with dysphagia, a widely used evidence-based food insecurity screener. Conclusions: There is a lack of understanding and evidence-based guidelines on how to address social determinants of health, one of which is food insecurity in older adults with dysphagia. Socially responsive speech-language pathology services require greater knowledge of the role of food insecurity in dysphagia intervention. Future research would benefit from a provider survey of medical speech-language pathologists to identify the current needs, trends, and systemic barriers related to food insecurity in clinical practice.